KEANEKARAGAMAN JENIS TUPAI (Tupaiidae) DALAM KAWASAN GUNUNG SEMAHUNG DESA PALO’AN KECAMATAN SENGAH TEMILA KABUPATEN LANDAK Diversity Of Squirrel (Tupaiidae) in Mount Semahung Palo’an Village Sengah Temila Landak District - diktus, Bene; dina, Wah; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2014)
This study aims to determine the squirrel (Tupaiidae) species diversity in Hutan Lindung Gunung Semahung Palo'an Village Sengah Temila Landak District. Using line method, with length 500 m and width 100 m, the plots were taken  purposively where the Tupaiidae is found. Tupaiidae identification using Mammals Field Guide (Payne et al,.1985), and local people. There are 3 species of Tupaiidae found in Hutan Lindung Gunung Semahung Palo'an Village namely: Tupaia minor, T.splendidula, T.gracilis, and total of 190 individuals. In the lowland area,  there were 3 species of Tupaiidae were found (106 individuals), whereas in the hilly area 2 species were found (84 individuals), T.gracilis were not found in the hilly area. The Tupaiidae diversity in the area is low, showed by the diversity index below 1 (H=0,8950). Dominance index C=0,4383, means that more than one species of Tupaiidae are dominant in the area that is;T.minor and T.splendidula. Richness index D=1,5071. Evenness index is low (e=0.8146) means individuals of each species are not even, there are two dominant species (T.minor and T.splendidula), and the individuals of T.gracilis is low and only found in lowland area. Further observations are needed to obtain more comprehensive information about Tupaiidae.Keywords : Tupaiidae, species diversity, protection forest Mount Semahung